OPERCULECTOMY; MINIMALY INVASIVE PROCEDURE TO TREAT OPERCULITIS/ PERICORONITIS IN IMPACTED THIRD MOLARS - Ramadhita Paramananda Prayudha; Sharah Shafira P.U (Journal of Health and Dental Sciences, 2026)
A significant proportion of third molars are impacted, with a prevalence ranging from 16.7% to 68.6% within the population. This condition often leads to inflammation of the occlusal surface, known as pericoronitis, which manifests as pain, swelling, and tenderness. In the this case, a 23-year-old woman presented with swelling and pain in the lower right molar region. Clinical examination revealed a Class I, Level A, vertical impaction with disto-occlusal pericoronitis of tooth 48. The proposed treatment plan included an operculectomy, a minimally invasive surgical procedure aimed at removing the operculum tissue from the tooth 48. Postoperative intraoral examination revealed pink gingiva, absence of swelling, and no bleeding upon probing, indicating the absence of postoperative complications. The patient reported no pain, and there was no recurrence of pericoronitis in the tooth 48. These findings suggest that operculectomy is a minimally invasive treatment option for managing symptoms associated with pericoronitis DOI : 10.54052/jhds.v6n1.p25-38